Body composition and risk for metabolic alterations in female adolescents - Eliane Rodrigues de Faria; Cristiana Araújo Gontijo; Sylvia do Carmo C. Franceschini; Maria do Carmo G. Peluzio; Silvia Eloiza Priore (Sociedade de Pediatria de São Paulo, 2014)
OBJECTIVE: To study anthropometrical and body composition variables as predictors of risk for metabolic alterations and metabolic syndrome in female adolescents.METHODS: Biochemical, clinical and corporal composition data of 100 adolescents from 14 to 17 years old, who attended public schools in Viçosa, Southeastern Brazil, were collected.RESULTS: Regarding nutritional status, 83, 11 and 6% showed eutrophia, overweight/obesity and low weight, respectively, and 61% presented high body fat percent. Total cholesterol presented the highest percentage of inadequacy (57%), followed by high-density lipoprotein (HDL - 50%), low-density lipoprotein (LDL - 47%) and triacylglycerol (22%). Inadequacy was observed in 11, 9, 3 and 4% in relation to insulin resistance, fasting insulin, blood pressure and glycemia, respectively. The highest values of the fasting insulin and the Homeostasis Model Assessment-Insulin Resistance(HOMA-IR) were verified at the highest quartiles of body mass index (BMI), waist perimeter, waist-to-height ratio and body fat percent. Body mass index, waist perimeter, and waist-to-height ratio were the better predictors for high levels of HOMA-IR, blood glucose and fasting insulin. Waist-to-hip ratio was associated to arterial hypertension diagnosis. All body composition variables were effective in metabolic syndrome diagnosis.CONCLUSIONS: Waist perimeter, BMI and waist-to-height ratio showed to be good predictors for metabolic alterations in female adolescents and then should be used together for the nutritional assessment in this age range.